2010
DOI: 10.1016/j.jpba.2010.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microdialysis sampling calibration approaches for lipophilic analytes: Doxorubicin

Abstract: Microdialysis is an important sampling technique in many pharmacokinetics and pharmacological studies. Applying microdialysis to lipophilic analytes can be difficult as low extraction efficiencies are generally obtained with these types of analytes. In this investigation, the effects of applying microdialysis to the lipophilic compound, doxorubicin are discussed. Using varying concentrations of doxorubicin (DOX) from 1 to 20 μM, in vitro probe calibrations were performed by delivery, recovery and no-net flux. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The no-net-flux (NNF) method used for probe calibration in vivo involves both recovery and delivery experiments in the same trial (21). The recovery determined in vivo was used to correct the actual interstitial concentrations from the subjects.…”
Section: Chemicals Levofloxacin Hydrochloride Ciprofloxacin (Internmentioning
confidence: 99%
“…The no-net-flux (NNF) method used for probe calibration in vivo involves both recovery and delivery experiments in the same trial (21). The recovery determined in vivo was used to correct the actual interstitial concentrations from the subjects.…”
Section: Chemicals Levofloxacin Hydrochloride Ciprofloxacin (Internmentioning
confidence: 99%
“…In Whitaker & Lunte's experiments [7], E D of the target compound, doxorubicin, was significantly higher than E R , which was ascribed to its strong absorption to membrane. The probe membrane became and remained red in color after perfusion also proved its absorption visually.…”
Section: Influence Of Drug Concentration On E D and E Rmentioning
confidence: 88%
“…Key: ■ = delivery of 10 mm membrane; □ = recovery of 10 mm membrane; ▲= delivery of 2 mm membrane; △ = recovery of 2 mm membrane Whitaker and Lunte [7] found that the absorption of the membrane led to the difference between E D and E R . It was not feasible to replace E R with E D when adsorption existed.…”
Section: Figmentioning
confidence: 99%
“…In Whitakers experiments [7], the E D of the target compound, doxorubicin, was significantly higher than E R , which was ascribed to its strong absorption to membrane. The probe membrane became and remained red in color after perfusion also proved its absorption visually.…”
Section: Influence Of Drug Concentration On E D and E Rmentioning
confidence: 89%
“…Whitaker [7] found that the absorption of the membrane led to the difference between E D and E R . It was not feasible to replace E R with E D when adsorption existed.…”
Section: Discussionmentioning
confidence: 99%